Optimization of ammonia removal by natural zeolite from aqueous solution using response surface methodology - Mokhtari-Hosseini Zahra Beagom; Kazemiyan Ehsan; Tayebee Reza; Shenavaei-Zare Toktam (Hemijska Industrija, 2016)
Ammonium removal from aqueous solution was investigated using natural zeolite. Operating variables were optimized by statistical design for this process. Eight variables including pH, contact time, dose and size of adsorbent, initial ammonia concentration, temperature, agitation and concentration of other adsorbate were screened by Placket-Burman design. The results indicated particle size, contact time, dose of zeolite and initial ammonia concentration are effective on removal efficiency with p-value<0.02. Optimizations of three important factors were conducted by response surface method. The optimal condition of ammonia removal in terms of removal efficiency was found to be at 0.18-0.4 mm particle size, 4 min contact time and 111 g L-1 dose of zeolite. The removal efficiency was found to be 98.25% at optimal condition. The maximum adsorption capacity of ammonium was 1.276 mg g-1 that was obtained at 0.18-0.4 mm zeolite size, 60 min contact time and 20 g L-1 zeolite dosage. The Langmuir and Freundlich isotherms adequately described the adsorption of ammonium ions by HCl-modified natural zeolite.